Comparing Turn Taking in Sessions of Different Courses - Laila, Malikatul; Haryanti, Dwi; Haryanto, Sigit (Prosiding University Research Colloquium, 2023)
The study discusses the turn taking made by lecturers and students during the online learning process. This study aims to find turn taking variations through online learning in university classroom sessions in the midst Covid-19 break. The research data are series of speeches in online learning in university classroom sessions collected from three different lectures session discourses produced by lecturers and students through Zoom and Google Meet. Data collection were done by using record and note taking techniques. Data were analyzed by applying the theory of turn taking rules of Sacks, Schegloff, & Jefferson's theory (1978). The results show that the variations of turn taking as in the online session as the application of rule 1 are dominated on the speaker teacher’s combining opinion or questions by confirming. In the meantime, the application of rule 3 is dominated on the speaker teacher’s self-repair. The use of teacher’s opinions and self- repair is implied to give a help to students for comprehending the online course.